GERD in the NICU Infant: Who needs to be treated and what approach is beneficial? - Gulati, Ish K. (Pediatr Clin North Am, 2019)
In this review, we discuss gastroesophageal reflux (GER) and gastroesophageal reflux disease (GERD) as it pertains to the infant in the NICU based on research in this specific population. Specifically, we summarize the developmental biology of the gastroesophageal junction (GEJ), the physiology of GER and the pathophysiology of GERD in the NICU infant setting, and identify risk factors for GER and GERD. We also address the epidemiology, economic burden and controversies surrounding GERD in the NICU infant, and formulate an approach to GER and GERD in his patient population. Finally, we examine the recent advancements in the individual assessment of GER and GERD in the NICU infant, and provide evidence-based guidelines that can be adopted.